Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Statistika MTs Kelas VIII - Bila Aprilia (Universitas Muhammadiyah Enrekang, 2020)
This study aims to analyze students' mistakes in completing statistical questions for class VIII, using qualitative descriptive research with the method of collecting data, and using test questions while the validity of the data by means of the test validity. This subject is 21 people. This research was conducted to students of class VIII Madrasah Tsanawiyah At-Taqwa West Bandung Regency academic year 2019/2020. The results of this study revealed that errors experienced by students varied including: 1) presenting statistical reports in the form of diagrams, either bar or circle diagrams; 2) determine the average value of a story and diagram problem; 3) determine the profit (%) by finding the average. While the error factors that can affect students in solving statistical material problems are: lack of initial understanding of the material about statistics, student motivation in following the teaching and learning process, learning with the model that is done is less motivating students to learn creatively and actively in understanding statistics subject matter.